Allosteric Modulation of GABAA Receptors by an Anilino Enaminone in an Olfactory Center of the Mouse Brain - Thomas Heinbockel; Ze-Jun Wang; Patrice L. Jackson-Ayotunde (MDPI AG, 2014)
In an ongoing effort to identify novel drugs that can be used as neurotherapeutic compounds, we have focused on anilino enaminones as potential anticonvulsant agents. Enaminones are organic compounds containing a conjugated system of an amine, an alkene and a ketone. Here, we review the effects of a small library of anilino enaminones on neuronal activity. Our experimental approach employs an olfactory bulb brain slice preparation using whole-cell patch-clamp recording from mitral cells in the main olfactory bulb. The main olfactory bulb is a key integrative center in the olfactory pathway. Mitral cells are the principal output neurons of the main olfactory bulb, receiving olfactory receptor neuron input at their dendrites within glomeruli, and projecting glutamatergic axons through the lateral olfactory tract to the olfactory cortex. The compounds tested are known to be effective in attenuating pentylenetetrazol (PTZ) induced convulsions in rodent models. One compound in particular, KRS-5Me-4-OCF3, evokes potent inhibition of mitral cell activity. Experiments aimed at understanding the cellular mechanism underlying the inhibitory effect revealed that KRS-5Me-4-OCF3 shifts the concentration-response curve for GABA to the left. KRS-5Me-4-OCF3 enhances GABA affinity and acts as a positive allosteric modulator of GABAA receptors. Application of a benzodiazepine site antagonist blocks the effect of KRS-5Me-4-OCF3 indicating that KRS-5Me-4-OCF3 binds at the classical benzodiazepine site to exert its pharmacological action. This anilino enaminone KRS-5Me-4-OCF3 emerges as a candidate for clinical use as an anticonvulsant agent in the battle against epileptic seizures.